Analysis of within-individual variation in extrapair paternity in blue tits (Cyanistes caeruleus) shows low repeatability and little effect of changes in neighborhood. (1st October 2020) - Beck, Kristina B; Valcu, Mihai; Kempenaers, Bart
Abstract: Many studies investigated variation in the frequency of extrapair paternity (EPP) among individuals. However, our understanding of within-individual variation in EPP remains limited. Here, we comprehensively investigate variation in EPP at the within-individual level in a population of blue tits ( Cyanistes caeruleus ). Our study is based on parentage data comprising >10 000 genotyped offspring across 11 breeding seasons. First, we examined the repeatability of the occurrence of EPP, the number of extrapair offspring, the number of extrapair partners, and the occurrence of paternity loss using data from males and females that bred in multiple years. Second, we tested whether within-individual changes in EPP between breeding seasons relate to between-year changes in the local social environment. Repeatabilities were generally low but significant for the occurrence and number of extrapair young in females and for whether a male sired extrapair young or not. We found no evidence that the presence of the former social partner or changes in the proportion of familiar individuals or in phenotypic traits of the neighbors influenced changes in levels of EPP in females. However, in adult males, a decrease in the average body size of male neighbors was associated with higher extrapair siring success. If confirmed, this result suggests that the competitive ability of a male relative to its neighbors influences his extrapair mating success. We suggest that alternative hypotheses, including the idea that within-individual changes in EPP are due to "chance events" rather than changes in an individual's social breeding environment, deserve more consideration. Abstract : Why do individuals vary in extrapair behavior? We examined the within-individual variation in extrapair paternity (EPP) across 11 seasons in a population of blue tits. We show that measures of EPP show low repeatability and that changes in the breeding environment explained only little of the changes in EPP. Thus, alternative hypotheses, including the idea that variation in EPP depends on "chance events, " should be considered.